The Avant-garde in Cuba: the Role of the revista de avance and the Utopia of Nation and Identity (Palimpsesto, 2018)
The 1920s and 1930s in Latin America saw an awakening of the artistic movement, influenced by theEuropean one. In countries such as Mexico, Brazil, Argentina and Peru, new voices began to take part innew and radical discourses. Cuba, from 1927 to 1930, published the journal Revista de Avance, whichoffered a renewed proposal in the field of arts and letters. This article analyzes the validity and importanceof this review. It was and is a fundamental reference to understanding the facts about publication during this time as well subsequent events, such as the success of the Cuban Revolution. The article lays out anoverview of the Revista de Avance. Specifically, it describes its content, both as militant andcosmopolitan. In addition, the author takes time to comment on graphic design, style, and the reproductionof pictures and other expressions from distinguished artists.Finally, this overview provides a glimpse of the cultural life at the end of the 1920s as well as thesociopolitical and economic visions of the time. Both visions contribute to know better this avant-gardepublication, particularly from its own idea of changing the status quo.
Keywords: Cuba; revista de avance; Latin American avant-garde; Caribbean Literature; Arts and Letters